Influence of Inclined Magnetic Field on the Peristaltic Flow of a Jeffrey Fluid in an Inclined Porous Channel - Jagadeesh, V.; Sreenadh, S.; Lakshminarayana, P. (International Journal of Engineering and Technology, 2018)
In this paper we have studied the effects of inclined magnetic field, porous medium and wall properties on the peristaltic transport of a Jeffry fluid in an inclined non-uniform channel. The basic governing equations are solved by using the infinite wave length and small Reynolds number assumptions. The analytical solutions have obtained for velocity and stream function. The variations in velocity for different values of important parameters have presented in graphs. The results are discussed for both uniform and non-uniform channels.Â